Examination of Thinking Styles of Turkish and English Prospective Teachers According to Mental Self-government Theory - Günseli Orhon; Adile Değirmenci; Abdulkadir Kurt; Muhammed Akıncı (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The aim of this study is to determine thinking styles of prospective teachers who study in Faculty of Education, Turkish Education and English Language Teaching Departments. The study is a quantitative research in which descriptive survey method was used. The data of the study was collected through Thinking Styles Inventory from a total of 154 prospective teachers who study in Akdeniz University, Faculty of Education, Turkish Education and English Language Teaching Departments. Stratified sampling technique was applied to determine the sample of this research. As collected data provided normality One-way ANOVA and Independent Samples T Test were used in data analysis processes. When Thinking Styles Inventory scores of prospective teachers were examined it was seen that the order of the highest scores are from Legislative, Judicial and Hierarchical thinking styles and the lowest scores were from Conservative, Global and Oligarchic thinking styles. Although the scores from the Thinking Styles Inventory show significant differences according to various variables the overall score distribution levels are close to each other for all dimensions according to the results of the research. In fact, this situation shows that Turkish and English prospective teachers tend to all thinking styles to some extent. In this context curriculums can be prepared for all students starting from the lowest level that provide educational environment in which they can develop their thinking styles.